Idiopathic intramural hematoma of the right colon. A case report and review of the literature. (2019) - Vecchio, Rosario; Cacciola, Emma; Figuera, Michele; Catalano, Renato; Giulla, Giuseppe; Distefano, Emanuele Rosario; Intagliata, Eva
Highlights: A very rare case of spontaneous colon hematoma has been reported. The rarity of our case of colon hematoma is due to the fact that it is idiopathic. The topic is still under discussion in the Literature since the pathophysiology remains still unknown. Abstract: Introduction: Intestinal hematoma is usually observed after an abdominal trauma or in patients treated with anticoagulant therapy. Conversely, idiopathic bowel hematoma is very rare, being colon involvement sporadic with few reports in the Literature. Presentation of case: The Authors report a case of idiopathic spontaneous large bowel hematoma. A 48-year-old man was admitted for a thoraco-abdominal pain and signs of acute abdomen and fever. After ruling out heart diseases, a CT scan revealed a marked thickening of the ascending colon wall, obstructing the bowel lumen. Leukocytosis was observed. In an emergency setting, an explorative laparotomy was performed. Hemoperitoneum and a large hematoma involving the caecum and the ascending colon were detected, together with intramesenteric and retroperitoneal blood effusion. A right hemicolectomy was accomplished. Histopathology confirmed the diagnosis of large bowel hematoma. Post-operative molecular diagnostic testing for coagulative disorders failed to demonstrate any genetic variation associate with hemorrhagic predisposition. In the post-operative course, the patient experienced a left basal bronco-pneumonia with increased unilateral pleural effusion, successfully treated by a thoracic drain and antibiotic therapy. Discussion: The reported case and Literature data show that diagnosis of idiopathic colon intramural hematoma is challenging, especially in the emergency setting. Although conservative therapy is the first line treatment, surgery still has an important role when the diagnosis is uncertain, medical treatment fails or a complication, such untreatable bleeding, perforation or occlusion occur. Conclusion: The Authors report a very rare case of spontaneous intramural hematoma of the right colon. Surgery still has a role in selected cases.